Effects of Service Learning on Physical Education Teacher Education Students’ Subjective Happiness, Prosocial Behavior, and Professional Learning - Chiva-Bartoll, Oscar; Montero, Pedro Jesús Ruiz; Capella-Peris, Carlos; Salvador-García, Celina (Frontiers in Psychology, 2020)
Purpose: This study aims to analyse the effects of a Service-Learning (SL) programme on the Subjective Happinnes (SH), Prosocial Behaviour (PB) and Professional Learning (PL) perceptions of Physical Education Teacher Education (PETE) students, as well as to examine the correlations among these variables. Method: The study used a quasi-experimental design of two non-equivalent groups (control and experimental) comparing pretest and posttest data. Instruments used were the Subjective Happiness Scale (SHS), the Prosocial and Civic Competence (PCC) questionnaire, and the Impact of Service-Learning during Initial Training of Physical Activity and Sports (IMAPS-AFD-FI) questionnaire. Results: Data indicated that SL only had significant influence in SH when students compared themselves with their peers. On the other hand, the effect of SL on promoting PB and PL perceived was significant in several of their dimensions. Finally, the results showed a greater correlation of the perceived PL with the PB than with the SH. Discussion/Conclusion: The results of the study provide educational researchers with valuable information to better understand how SL influences the training of PETE students.